To Stay or to Leave? The Views of Managers and Consultants in Management Consulting Sector - Tillou, Caroline; Al Ariss, Akram (Management international / International Management / Gestiòn Internacional)

(untitled) (HEC Montréal, 2022)
Retaining knowledge workers is of foremost interest to both academics and managers. This article conducts a deep analysis identifying prevailing HR retention practices and linking them to the AMO framework, which represents employees’ needs in terms of abilities, motivation, and opportunities for future retention. This exploratory research relied on the contributions of managers and employees from 17 French management consulting firms. The findings show the role of interpersonal internal and external relationships in times of retention of this population. This research elucidates how the ambivalence of consultants-customers’ relationships can be either facilitating or binding in such context.